PENGARUH STRUKTUR MODAL DAN STRUKTUR KEKAYAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Clara Yulia Kekado; Hironnymus Jati (Universitas Nusa Cendana, 2018)
This study aims to examine the influence of Capital Structure and Wealth Structure on theFinancial Performance of Telecommunication companies listed on the Indonesia Stock Exchange.Dependen variable in this research is Financial Performance of company. The company’s FinancialPerfomance is measured by Return On Equity (ROE). The independent variable in this study is theCapital Structure measured by Debt to Equity Ratio (DER) and Wealth Structure measured byCurrent Asset to Fixed Asset (CTF). The population in this study includes all Telecommunicationcompanies listed on the Indonesia Stock Exchange in 2012-2017 and all populations are taken asresearch samples because the number of Telecommunications companies only amounted to 5companies or saturated samples. Data Analysis is Multiple Linear Regression using panel data orcalled panel data regression model.The result of research shows that Capital Structure and WealthStructure have positive and significant influence simultaneosly on Financial Performance withFarithmetic 16,48 at significant level 0,00<0,05. Adjusted-R square value of 0,516 shows the capitalStructure And Wealth Structure is able to explain the Financial Performance of 52% and theremaining 48% is explained by other variables outside the research model. It is suggested to set theproblem of debt because it does not have a significant effect on Financial Performance while theliquidity needs to be maintained because it has a significant effect on the Financial Performance ofthe company.Keywords : Capital Structure, Wealth Structure, Financial Performance, Debt To Equity Ratio,Current Asset To Fixed Asset, Return On Equity.